THE STUDENTS’ ABILITY IN PRONOUNCING ENGLISH PALATO ALVEOLAR FRICATIVE ([Ʃ], [Ʒ]): A CASE STUDY OF SMA N 12 SEMARANG - Maghdalena Susanto; Pasca Kalisa (Universitas Negeri Manado, 2023)
Pronunciation is an essential aspect of speaking skills in learning English since learning a language aims to communicate, and mispronunciation can lead to misunderstanding. Indonesian students might still find difficulties in pronouncing English sounds, such as English palato alveolar fricative sounds that do not exist in Bahasa Indonesia. This study analyses the students’ mastery of pronouncing English palato alveolar fricative sounds. The objective of this study are to find out the level of the students’ ability to pronounce English palato alveolar fricative sounds ([ʃ] and [ʒ]) and the factors causing errors among the students in pronouncing English palato alveolar fricative sounds. The subject is the 60 eleventh-grade students of SMA Negeri 12 Semarang. The instruments are the spoken test containing words of English palato alveolar fricative consonant sounds and the interview question as additional data. To determine the achievement, the researcher uses the level of criterion by Tinambunan. Based on the data analysis of the spoken test, the percentage of the students’ mastery in producing the sounds is 40%, considered as fair. According to the interview result, the factors causing the students’ pronunciation errors are attitude and motivation, exposure to the target language, language interference, and orthographic writing.